Are metals and pyrene levels additional factors playing a pivotal role in air pollution-induced inflammation in taxi drivers?. Issue 1 (7th November 2017) - Gauer, Bruna; Brucker, Natália; Barth, Anelise; Arbo, Marcelo D.; Gioda, Adriana; Thiesen, Flávia V.; Nardi, Jessica; Garcia, Solange C.
Graphical Abstract: Abstract: This study aimed to evaluate which xenobiotic (As, Hg, Pb or pyrenes) is primarily responsible for the inflammatory process in taxi drivers. Multiple regression analysis showed that Hg is the main xenobiotic responsible for the increase of cytokine levels. These associations suggest that co-exposure to pollutants could be a risk factor for health effects.